Probabilistic Seismic Demand Model and Seismic Fragility Analysis of NPP Equipment Subjected to High- and Low-Frequency Earthquakes. (2nd December 2021) - Tran, Thanh-Tuan; Le, Thi-Mai-Trang; Nguyen, Phu-Cuong; Kim, Dookie; Pham, Thong M.; Salman, Kashif; Chang, Seongkyu
Abstract: This study presents the Probabilistic Seismic Demand Model (PSDM) and explores optimal intensity measures (IMs) for nuclear power plant (NPP) equipment when subjected to ground motions having high-frequency (HF) and low-frequency (LF) contents. To this end, the PSDM is first constructed in terms of the IM and the corresponding engineering demand parameter, and its outcomes are utilized to select the optimum IMs based on the satisfaction of certain essential properties (i.e., efficiency, practicality, and proficiency). Regarding earthquake excitation, different IMs (i.e., structure-independent and structure-dependent IMs) are studied. The results show that the most appropriate IMs for the seismic performance of the cabinet are velocity spectrum intensity and spectral accelerations for the structure-independent IMs and the structure-dependent IMs, respectively. Moreover, fragility analysis is performed to assess the vulnerability of NPP equipment. The outcomes indicate that the cabinet is highly vulnerable to HF earthquakes as a consequence of response amplification. In addition, the selection of the earthquake IM has an important influence on the collapse capacity of the cabinet, and the fragility curves obtained from structure-dependent IMs are more reliable in comparison to those of structure-independent IMs.